2020
DOI: 10.1111/jipb.12897
|View full text |Cite|
|
Sign up to set email alerts
|

Lectin receptor kinase OsLecRK‐S.7 is required for pollen development and male fertility

Abstract: Pollen grains are covered by exine that protects the pollen from stress and facilitates pollination. Here we isolated a male sterile mutant s13283 in rice exhibiting aborted pollen with abnormal exine and defective aperture. The mutant gene encodes a novel plasma membrane‐localized legume‐lectin receptor kinase that we named OsLecRK‐S.7. OsLecRK‐S.7 was expressed at different levels in all tested tissues and throughout anther development. In vitro kinase assay showed OsLecRK‐S.7 capable of autophosporylation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…their extracellular domain motifs [6,7]. For instance, the leucine-rich repeat receptor kinases (LRR-RKs) are the largest of the RK family in Arabidopsis and sense a diverse set of hormone signaling pathways to regulate cell proliferation and expansion, stomatal development and stem cell maintenance [5,[8][9][10].…”
mentioning
confidence: 99%
“…their extracellular domain motifs [6,7]. For instance, the leucine-rich repeat receptor kinases (LRR-RKs) are the largest of the RK family in Arabidopsis and sense a diverse set of hormone signaling pathways to regulate cell proliferation and expansion, stomatal development and stem cell maintenance [5,[8][9][10].…”
mentioning
confidence: 99%
“…However, other sporophytic cellular defects among these allelic mutants were highly variable. For example, the pollen exine was thickened in s13283 grains (Peng et al, 2019), while the ap1 (Fig. 6, Fig.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that the sporophytic defects of ap1 cannot be seen, but are sufficient to alter fertility. Very recently, three other allelic mutants of AP1 were reported: s13283 (in the background of the indica cultivar Huanghuazhan), oslecrk5 (in the background of the japonica cultivar 02428) and defective in aperture formation1 (osdaf1; in the background of the japonica cultivar 9522) (Peng et al, 2019;Wang et al, 2020;Zhang et al, 2020). We carefully compared the cytological characteristics of these allelic mutants and found that they all showed the following identical features: shrinking pollen grains with gametophytic defects (less or no cellular content and absence of pollen intine layer) and sporophytic defects (abnormal aperture morphology).…”
Section: Discussionmentioning
confidence: 99%
“…Two other LecRLKs, OsSIK2 in rice and GsSRK in soybean can both be induced by ABA treatment and contribute to plant architecture, while the former also delays dark-induced senescence in rice Sun et al, 2018). Moreover, OsLecRK-S.7 in rice and LecRK-IV.2 in Arabidopsis are required for pollen development and the former is also responsible for male fertility (Wan et al, 2008;Peng et al, 2019). Although most of these findings on the involvement of LecRLKs in plant development still need further investigation to provide a clear picture, one clue is that plant hormones, especially ABA and GA, are in close association with the function of LecRLKs in plant growth and development.…”
Section: Lecrlks In Plant Developmentmentioning
confidence: 99%